2017
DOI: 10.1246/cl.170692
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical H2 Evolution Catalyzed by Porphyrin-based Cubic Cages Singly and Doubly Encapsulating PtCl2(4,4′-dimethyl-2,2′-bipyridine)

Abstract: A porphyrin-based cubic cage (Cube) was reacted with a Pt(II)-based molecular H 2 -evolving catalyst, PtCl 2 (dmbpy) (PtDmb; dmbpy: 4,4¤-dimethyl-2,2¤-bipyridine), to give Cubes incorporated with one or two equivalents of PtDmb, i.e., Cube(PtDmb) and Cube(PtDmb) 2 , which was confirmed by ESI-TOF MS spectroscopy. A photochemical H 2 -evolving system consisting of EDTA (sacrificial electron donor), [Ru(bpy) 3 ] 2+ (photosensitizer), and methylviologen (electron relay) was used to demonstrate that the catalyst e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Note that the one-electron-reduced species ( BV •+ ) is relatively stable, enabling to form a long-lived ET state in supramolecules. In addition, viologen derivatives have been often used as electron mediators in photocatalytic reduction reactions. Thus, we have employed a BV 2+ derivative having a carboxyl group ( BV 2+ COOH ) as an electron acceptor in a hydrogen-bonded supramolecular assembly with H 2 DPP , H 4 DPP 2+ (BV 2+ COO – ) 2 . We have examined the photodynamics of H 4 DPP 2+ (BV 2+ COO – ) 2 to confirm that H 4 DPP •+ acts as an electron mediator in the hydrogen-bonded supramolecule.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the one-electron-reduced species ( BV •+ ) is relatively stable, enabling to form a long-lived ET state in supramolecules. In addition, viologen derivatives have been often used as electron mediators in photocatalytic reduction reactions. Thus, we have employed a BV 2+ derivative having a carboxyl group ( BV 2+ COOH ) as an electron acceptor in a hydrogen-bonded supramolecular assembly with H 2 DPP , H 4 DPP 2+ (BV 2+ COO – ) 2 . We have examined the photodynamics of H 4 DPP 2+ (BV 2+ COO – ) 2 to confirm that H 4 DPP •+ acts as an electron mediator in the hydrogen-bonded supramolecule.…”
Section: Introductionmentioning
confidence: 99%
“…127 Following the same principle, Sakai and co-workers introduced molecular Pt(II) PRCs such as Pt II (dmb)Cl 2 (9) bearing π-conjugated ligands as guest into the cavity of C7 (Figure 11). 128 In addition to 3a as PS and ethylenediaminetetra acetic acid (EDTA) as sacrificial reductant, methyl viologen (10) was used as electron relay in the photochemical system with [9⊂C7] as catalyst in aqueous acetate buffer at pH 5. The role of the redox mediator is to act as shuttle between PS and catalyst.…”
Section: Proton Reductionmentioning
confidence: 99%
“…The design of artificial photosynthetic systems that split water into molecular hydrogen and oxygen remains a major challenge of our times. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Explored extensively by Sakai and coworkers, [17][18][19][20][21][22][23][24][25][26][27][28] the photoreduction of water requires a photosensitizer, an electron relay and a hydrogen-evolving catalyst, either as a three-component system, 1,2 or with one [3][4][5][6][7][8][9][10] or two 11,12 multifunctional components. Sakai showed that Platinum(II) terpyridyl (tpy) chloride 1a can be used both as a photosensitizer and H 2 -evolving catalyst in the presence of ethylenediaminetetraacetic acid (EDTA) as the sacrificial electron donor.…”
Section: Introductionmentioning
confidence: 99%